COMPARISON ANALYSIS OF ENGINE PERFOMANCE BETWEEN CONVENTIONAL ENGINE (CARBURETOR) SYSTEM AND ELECTRONIC FUEL INJECTION (EFI) ENGINE SYSTEM OF TOYOTA KIJANG SERIES 7K-E - GUNAWAN, SAFRI (2011)
The research is presented to get the number of comparison for torque, power, and specific fuel consumption between conventional engine (carburetor) system and electronic fuel injection (EFI) engine system. The method that used to get the data is by using the experiment method. The research is begun by preparing tools and materials those will be used for making test bed. After that is assembling the system on the engine alternately after getting the data including voltage, current, engine rotation (rpm), and fuel consumption (ml). Based on the experiment and parameter those have been experimented, the engine performance on the conventional system is lower at the high engine rotation than electronic fuel injection system, and when the engine rotation is low, the engine performance of the conventional system is higher than electronic fuel injection system, and the specific fuel consumption on the conventional engine system at high engine rotation is more wastefully than electronic fuel injection system, but at low engine rotation, the conventional engine system is more economical than electronic fuel injection system.